Varietal Diallel Analysis for Yield and Yield Traits in Taramira (Eruca sativa L.) - Nehra, M R; Sastry, E V.D (Annals of Arid Zone, 2016)
A varietal diallel performed in taramira, indicated complex inheritance for seed yield and its component traits. The heterosis component accounted for more than 70%Â· of the total sum of squares, and among the heterosis components, the SCA component accounted for more than 70% to the total heterosis sum of squares. Trend between the Jlcr se performance and the varietal heterotic effects were reverse. The crosses involving RTM-465 or RTM-314 were the best for mean seed yield including yield traits and the SCA effects .